(untitled) (Conferencea, 2021)
The article employment is the activity of citizens related to the satisfaction of personal and social needs, which brings them income in monetary or other form. It is characterized by a system of economic relations regarding the provision of jobs for citizens and the definition of forms of participation in the public economy in order to obtain a livelihood. The type of employment is determined by certain principles of organization, stimulation and remuneration, internal and external industrial relations. In the conditions of the formation of a market economy, views on the so-called principle of universality of labor as an attribute of extensive economic development are changing. Market relations provide for a person’s free choice of profession and place of work in accordance with his abilities, voluntary employment of citizens, do not allow forced labor in any form, except in cases provided for by the legislation of the country. In these conditions, the problem of full employment and its effectiveness arises in a new way